(3GdehGLgI GdLfGFjI dLQGFe NWa GdCWaGd ai GdJTQjY GdLRGFQi (B: s (3OQGSI ebGQfI (B/ s - (3TQjaI HhHcQs; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JYJHQ LQjeI NWa GdCWaGd ef CNWQ GdehGVjY GdJi HQRJ ai GdacQ GdbGfhfi h GdGLJeGYi(B: (3HMjK GfJTGQgG h HdhZgG OQLI cHjQI ef GdNWhQI(B: (3LYdJ ecGaMJgG Ydi GdeSJhi GdhWfi h GdOhdi CeQG VQhQjG dG jecf GdJZGVi Yfg(B: (3HGYJHGQ GdWad gh Gdechf GdCSGSi ddCSQI h GdeLJeY aGUHM GdGgJeGe HGdGWaGd eDTQG MVGQjG JJSGHb ajg GdTYhH h GdOhd(B: (3JSf GdYOjO ef GdJTQjYGJ GdNGUI HMeGjJge h VeGf Mbhbge h cPG GdOaGY Yf bVGjGge(B: (3HMjK GdGYJOGA Ydjge HeKGHI GYJOGA UGQN Ydi GdGef h GdScjfI GdYGeI ddeLJeY(B. (3GdGeQ GdPi LYd GdeTQY GdLRGFQi jLJgO ef GLd hVY VeGfGJ cajdI dMeGjI GdWad ef GdGNJWGa h ef eNJda GTcGd GdGYJOGAGJ GdGNQi GdJi jJYQV dgG GdWad GdVMjI(B. (3h Pdc HGgejI JVGaQ LghO eNJda GdeDSSGJ h GdgjFGJ GdOhdjI (B((3GdGef(B: (3GdbVGA(B: (3GdGYdGe(B) (3eY GdeLQejf h JWHjb GbUi GdYbhHGJ Ydjge h GgejI GdJhYjI HeNGWQ gPg GdLQGFe h GKGQgG Ydi GdGaQGO h GdeLJeY h Ydi GdOhdI h SjGSJgGs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B352-372s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjY GdLRGFQis; (3LQGFe NWa GdCWaGds; (3bGfhf GdYbhHGJs; (3LQGFe GdVQQ s; (3CQcGf LQjeI GNJWGa GdCWaGd s; (3LQGFe GdeJGLQI s; (3eDSSGJ GdeLJeY GdeOfj s; (3GdeDSSGJ GdJQHjI s; (3LQjeI GdENaGA s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs